Experience of application of marketing technologies and the way of optimization of methodsof the brand management as the means providing competitiveness of the company (Путеводитель предпринимателя)
According to tendencies of development of marketing branding becomes the most effective remedy of ensuring competitive advantages of the company today. However, exhaustion of potential of traditional methods of advance of the goods, demands new technologies of the organization of process of creation and management of a brand.